The influence of employee competence and work environment on service quality - Sutarmo, Sutarmo; Indarti, Sri; Malta, Malta (Institute of Computer Science (IOCS), 2024)
The purpose of this study was to determine the effect of competence and work environment simultaneously on the quality of employee services at the Sabang City Port Authority Office. The type of research in this study is survey research, the research design used in this study is a correlational design to draw the influence between the independent variable (X) and the dependent variable (Y). The population in this study were all employees of the Sabang City Port Authority and Port Authority Office totaling 39 people, as well as being used as research samples. The results showed that the significance value (Sig) for the Competency variable was 0.628 and the calculated t value was 0.489 < t table (2.028) and the significance value (Sig) for the work environment variable was 0.257 and the calculated t value was -1.152 < t table (2.028). It can be concluded that there is no effect of competence and work environment on the quality of employee services at the Sabang City Port Authority Office